The relevance of muscle fiber type to physical characteristics and performance in team-sport athletes - Hopwood, H. J.; Bellinger, P. M.; Compton, H. R.; Bourne, M. N.; Minahan, C. (International Journal of Sports Physiology and Performance, 2023)
Purpose: The aim of this systematic review was to (1) determine the muscle fiber-type composition (or muscle fiber typology [MFT]) of team-sport athletes and (2) examine associations between MFT and the physical characteristics and performance tasks in team-sport athletes.